Preventive effect of foods enriched in natural conjugated linoleic acid on some metabolic alterations induced by high fat diets in rats - BernalL, Claudio; Gerstner, Carolina; Sain, Juliana; González, Marcela; Lavandera, Jimena; Scanarotti, Ignacio (2019)

(untitled)
Intake of high-fat (HF) diets has been associated with liver, muscle and adipose tissue lipid accretion and insulin resistance in humans and experimental animal models. c9,t11-conjugated linoleic acid (CLA), also known as rumenic acid (RA) and its precursor vaccenic acid (VA), naturally present on dairy products, showed to induce health benefits on lipid and carbohydrate metabolism.